2009
DOI: 10.1158/0008-5472.can-08-2694
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D and Risk of Pancreatic Cancer in the Prostate, Lung, Colorectal, and Ovarian Screening Trial

Abstract: Experimental evidence suggests that vitamin D has anticarcinogenic properties; however, a nested case-control study conducted in a population of male Finnish smokers found that higher 25-hydroxyvitamin D [25(OH)D], the best indicator of vitamin D status as determined by the sun and diet, was associated with a significant 3-fold increased risk for pancreatic cancer. We conducted a nested case-control study in the Prostate, Lung, Colorectal, and Ovarian Screening Trial cohort of men and women 55 to 74 years of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 46 publications
2
89
2
1
Order By: Relevance
“…In this study, we observed a stronger inverse association with vitamin D among nonsmokers and among those living in southern states. The PLCO study also found a significant interaction by geographic region (P interaction ¼ 0.015): they reported a positive association of risk with plasma vitamin D concentrations among those living in northern latitudes, but no association was observed among those living in southern latitudes (Stolzenberg-Solomon et al, 2009). Another difference in the ATBC study population concerns dietary pattern: a major dietary source of vitamin D in the Finns does not tend to be from fortified dairy products or breakfast cereal as American populations but from vitamin D-rich fish that may contain some pancreatic carcinogen such as organochlorine compounds (Stolzenberg-Solomon et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, we observed a stronger inverse association with vitamin D among nonsmokers and among those living in southern states. The PLCO study also found a significant interaction by geographic region (P interaction ¼ 0.015): they reported a positive association of risk with plasma vitamin D concentrations among those living in northern latitudes, but no association was observed among those living in southern latitudes (Stolzenberg-Solomon et al, 2009). Another difference in the ATBC study population concerns dietary pattern: a major dietary source of vitamin D in the Finns does not tend to be from fortified dairy products or breakfast cereal as American populations but from vitamin D-rich fish that may contain some pancreatic carcinogen such as organochlorine compounds (Stolzenberg-Solomon et al, 2006).…”
Section: Discussionmentioning
confidence: 91%
“…Higher dietary vitamin D intake as well as higher total vitamin D intake (from foods and supplements) was related to lower risk in the NHS and the HPFS (Skinner et al, 2006) but not in a cohort of male Finnish smokers enrolled in the AlphaTocopherol, Beta-Carotene (ATBC) Cancer Prevention Study (Stolzenberg-Solomon et al, 2002). Directly measured circulating (Stolzenberg-Solomon et al, 2009). In contrast, the vitamin D prediction score, which also accounts for sun exposure (by using residential state and physical activity as surrogates) and vitamin D intake, was inversely associated with pancreatic cancer risk in the present two US prospective cohort studies (NHS and HPFS) and this study).…”
Section: Discussionmentioning
confidence: 98%
“…The model of regulation represented by Figure 57 [19], pancreatic cancer [20,21], and mortality [22]. While it remains possible that U-shaped risk curves are extremes of the statistical noise observable for anything being studied intensely, the observations do show a pattern, in that they have only been reported for northerly populations, but not in the south.…”
Section: Hypothesis That Large Fluctuations In 25(oh) D Concentrationmentioning
confidence: 99%
“…However, a recent study showed that high vitamin D concentrations (from diet and sunlight exposure) were associated with a statistically significant 2-fold increase in PC [156] . The risk for PC was observed in subjects with low estimated annual residential solar UBV exposure but not in those with moderate to high yearly exposure [157] .…”
Section: Exposure To Sunlightmentioning
confidence: 96%